Pengaruh Kompensasi Bonus dan Dividen Payout Ratio Terhadap Praktik Perataan Laba: Studi pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Novita Anjasari; Wayan Ardani; Ni Putu Andini Desiyanti Laksmi (Jurnal Visi Manajemen, 2024)
This study aims to examine the effect of bonus compensation variables and dividend payout ratios on income smoothing in banking companies listed on the Indonesia Stock Exchange in 2021-2023. This study is a quantitative study using data in the form of numbers. The research data was obtained from second parties or secondary data, namely data obtained from the financial statements of each sample company. The population in this study were banking sector companies in 2021-2023 with the sample selection technique used being the non-probability technique, namely the perposive sampling technique. This technique is a sample selection technique that is carried out by providing sample criteria that can be used as samples in the study. The criteria used in selecting the sample are that the company publishes financial reports during the study period, the company makes a profit during the study period, the company provides dividends to shareholders during the study period and the company presents financial reports in rupiah. In this study, there were 16 companies that met the predetermined sample criteria using the perposive sampling method, so that the final total sample for the three years of the study was 48 samples. The data analysis techniques used consist of descriptive statistical tests, multiple linear regression tests, normality tests, heteroscedasticity tests, and hypothesis tests consisting of partial t tests, simultaneous f tests and determination coefficient tests. The results obtained in this study are that partially the bonus compensation variable does not have a significant effect on income smoothing, the dividend payout ratio variable has a significant effect on income smoothing and simultaneously the bonus compensation variable and the dividend payout ratio variable have a significant effect on income smoothing. Both of these variables are able to influence income smoothing by 25.2% which is a large enough number to provide a simultaneous effect.